2015
DOI: 10.11113/jt.v76.5684
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hybridization on Open-Hole Tension Properties of Woven Kevlar/Glass Fiber Hybrid Composite Laminates

Abstract: Hybrid laminates consisting of woven Kevlar/glass fiber composite plies were studied in terms of their residual tensile strength, stiffness and fracture surface.  Residual tensile strength and stiffness were determined from the open hole tension test according to ASTM D5766. The laminates of Kevlar fiber reinforced polymer (KFRP), glass fiber reinforced polymer (GFRP) and hybrid of Kevlar-glass fiber reinforced polymer (KGFRP) were fabricated using a vacuum bagging process. Three different ratios of Kevlar to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The scenario with the open hole is the topic of this research. Research into the open hole of hybrid composite laminates has been one of the recent focuses [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scenario with the open hole is the topic of this research. Research into the open hole of hybrid composite laminates has been one of the recent focuses [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Guled and Chittappa [ 30 ] into hybrid CF/Kevlar/Epoxy laminates concluded that using CF laminate on the outer skin enhances the interlaminar shear strength of the overall laminate. Shaari et al [ 20 , 21 , 23 ] studied the open-hole tension (OHT) test for Kevlar/glass fiber (GF)/epoxy fiber hybrid laminate composites for different hybridization ratios, hole sizes, and stacking sequences. The OHT of GF laminates improved due to the existence of Kevlar fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the popularity of the glass fibre reinforced polymer composites (GFRP ) use in aircraft and aerospace engineering industries, for a long time due to their high specific strength-to weight ratio, non-corrosive properties and have a very low strain-to-failure. 1 4 Accordingly, this is considered as a disadvantage for using these laminates under a tensile or/flexural loading conditions. 5 Additionally, in civil infrastructures, structural stability is a key factor that maintains a structure to be safe in usage under static or dynamic loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Kevlar has excellent mechanical properties such as high strength with lightweight, thermal stability and good resistances to abrasion resulting in wide use in aerospace, military applications, protective apparel and marine industry. 3 , 7 , 8 However, the major limitation for using them in the different sectors are their weaknesses in tensile, compression and bending loading. 9 One possible way to achieve better performance is by adopting a hybrid composite that is made up of two or more different fibres or resins.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrids comprising of continuous aramid/glass [25], and glass/carbon [26] fibre weaves can be optimised to achieve higher net strength retention than the nominal non-hybrid composites. Czél et al [27] investigated notch sensitivity of carbon/carbon pseudoductile hybrids.…”
Section: Introductionmentioning
confidence: 99%